Solução semicoletiva de tratamento de águas fecais e seu processo de apropriação em comunidade de área alagável da Amazônia - Joao Paulo Borges Pedro (2022)
In the Brazilian Amazon, only 14% of the municipalities are served with sanitation services. In the northern region of the country, which is entirely inserted in the Legal Amazon, 3.8 million people in rural areas do not have connections to the sewage system or septic tank. The natural environment itself constitutes a challenging environment for the implementation of sanitation technologies, given its flood pulse, which annually floods the plains of this region with an extreme amplitude between dry and flood of up to 12 meters. The literature review on sewage treatment technologies for flood prone areas points to a wide range of possible technological arrangements and makes it clear that there is no universal solution to this challenge. Based on this context, the study had the following objectives: a) Implementation of a sewage treatment technology (fecal water) in a community in a floodable area and evaluation of its suitability for natural flooding and; b) analysis of the appropriation of this technology by the users. For this,Action Research (AR) was used as a global methodological strategy, because of its potential to provide real changes in the context of the studied community. The main group of residents studied was the community of Santa Maria, located in a flooded area in the middle Rio Solimões region, in the state of Amazonas. As a result of the exploratory and planning phases, the participating community and families were selected. The characterization of the community environment and its socioeconomic profile were also carried out; and, selection, adaptation and implementation of the Fecal Water Treatment System (FWTS), with the active participation of community residents. The FWTS was the result of a survey and adaptation process of a sewage treatment system for the floodplain (flooded area). The main features of the system are: it is composed of a septic tank, an anaerobic filter, and a soak pit, the first two units being installed on a raised base allowing them to remain out of reach of the annual flooding of the river; and the arrangement is semi-collective, serving up to three families simultaneously, with a reduction in the per capita cost of installation. The main motivations identified for the adoption or continued use of toilets by residents were safety, privacy, comfort and protection. Regarding appropriation, this study proposed nine components of appropriation of social technologies. Among them, the feeling of acceptance, commitment, participation in the implementation of the technology, and informal education processes stood out as strong influencers in the process of appropriation of sewage treatment technology. From a methodological perspective, the AR proved to be a complex and demanding method to be carried out with the Tefé Municipality, which could not meet the actions defined by themselves and ended up finishing their participation in the project. At the same time, the AR presented alignment with the principles of the human right to sanitation, and the guiding principles of social technologies, notably with regard to social participation as a mandatory element. The research paved the way to the resolution of a real problem in the studied community, in addition to generating robust information to support the generation of regionalized public sanitation policies, such as information on the motivations and elements that lead to technological appropriation.